Pengaruh Motivational Interviewing Terhadap Self-Efficacy Penyalahguna Narkoba Di Klinik Pratama Adi Pradana BNN Provinsi Sulawesi Selatan - Nurdiana F Nahdalipa; Fatmah Afrianty Gobel; Yusriani (Journal of Muslim Community Health, 2021)
Backgorund: Problems arise due to the impact of drug abuse. Despair and decreased motivation to recover so that it has an impact on a person's self-efficacy which influences the individual to determine the actions that will be taken to achieve a goal including thinking about various events to be faced. Self- efficacy can also be influenced by several factors such as cognitive, affective, behavioral, and environmental. This study aims to analyze the effect of motivational interviewing on the self-efficacy of drug abusers at the Adi Pradana Primary Clinic BNNP South Sulawesi. Methods: This study used the Quasi Experiment method with the research design used was Pretest-Posttest with Control Group Design, with a total. Sampling technique with a total of 42 samples, consisting of 21 samples of the intervention group through counseling for three counseling sessions and the control group through brochures, analyzed. Using SPSS 26.0 with paired samples t-test and independent t-test. Results: The results of this study indicate that: There is an effect of counseling intervention on self-efficacy in drug abusers with a p value of 0.000 (p<0.05); There was no effect of giving brochures on self-efficacy for drug abusers with a p value of 0.883 (p> 0.05); There is no difference in self- efficacy for drug abusers in the two groups before being given intervention in the form of counseling and brochures where the p value is 0.193 (p>0.05), and there is a difference in self-efficacy for drug abusers after being given intervention with counseling techniques where the p value is 0.000 (p <0.05). Conclusion: The conclusion of this study is that there is an effect of giving intervention with counseling techniques on self-efficacy in drug abusers at the Adi Pradana Clinic, BNNP, and South Sulawesi.